Think write grow : how to become a thought leader and build your business by creating exceptional articles, blogs, speeches, books and more - Butler, Grant (Wiley, 2012)
In a competitive age, thought leadership has emerged as a subtle but powerful way to grow your business, establish credibility and demonstrate expertise, build your profile and forge relationships with prospects and customers. Thought leadership material can take many forms, including public speaking, websites, the media, advertising, writing books, online forums, webinars and blogging. This book will show you how to take your great ideas and craft them into a clear point of view which can influence others. The book is organised into three parts: 1. Think: Defines thought leadership and how to.